2011
DOI: 10.1029/2011jc007386
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic eddy formation and propagation southwest of Taiwan

Abstract: [1] Oceanic eddies are active and energetic southwest of Taiwan. The formation and propagation of eddies in this area were investigated using 17 year satellite altimeter data. Cyclonic eddies (CEs) and anticyclonic eddies (ACEs) often coexisted, but there were more CEs than ACEs generated during the period from October 1992 to October 2009. ACEs were stronger and, in general, lived longer than CEs. ACEs occurred more often in winter than in other seasons, while CEs were more frequent in summer. Compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 43 publications
6
83
0
Order By: Relevance
“…In 2005, the AE was extremely strong, and simultaneously, T4 and WW were also larger than other times. Similar as that pointed out by Nan et al (2011c), Kuroshio instability is more important than direct wind effects on the AE formation southwest of Taiwan. However, periodical variation of the wind reinforce the Kuroshio variability, and the wind stress work on the mean flow could also be transferred to the EKE through BTI.…”
Section: Barotropic Instability and Direct Wind Stress Worksupporting
confidence: 80%
See 4 more Smart Citations
“…In 2005, the AE was extremely strong, and simultaneously, T4 and WW were also larger than other times. Similar as that pointed out by Nan et al (2011c), Kuroshio instability is more important than direct wind effects on the AE formation southwest of Taiwan. However, periodical variation of the wind reinforce the Kuroshio variability, and the wind stress work on the mean flow could also be transferred to the EKE through BTI.…”
Section: Barotropic Instability and Direct Wind Stress Worksupporting
confidence: 80%
“…5). The correlation of the eddy generation (indicated by eddy-occupied areas) southwest of Taiwan with the Kuroshio path variability (indicated by geostrophic vorticity) and local wind forcing (indicated by the wind stress curl) suggested that Kuroshio was a more important factor for eddy generations (Nan et al 2011c). But their relative importance during the development of an eddy had not been quantitatively discussed yet.…”
Section: Energy Analysismentioning
confidence: 99%
See 3 more Smart Citations